Set-based concurrent engineering process model and systematic application on an electronic card reader - Al-Ashaab, Ahmed; Araci, Zehra Canan; Maulana, Muhd Ikmal I. Mohd; Garcia Almeida, Cesar; Young, Steve (World Scientific and Engineering Academy and Society (WSEAS), 2021)
Set-based concurrent engineering (SBCE), also known as set-based design, is a state-of-the-art approach to the new product development process. SBCE, simply, provides an environment where designers explore a wide range of alternative solutions in the early stages of product development. After gaining knowledge, solutions are narrowed down until the optimal solution is ensured. Such an environment saves considerable amount of cost and time while reaching innovation and high quality in the products. However, industrial practitioners seek a clear and systematic application throughout an SBCE process. This paper demonstrates a well-structured SBCE process model and its step-by-step application on a product called “electronic card reader”. Real data is used in the industrial case study. Results showed the benefits of applying SBCE in both the product, and the process of new product development.
Keywords: New product development; Lean product development; lean thinking; Set-Based Concurrent Engineering; Knowledge Reuse; Innovation